Fruits and vegetables intake and its subgroups are related to depression: a cross-sectional study from a developing country - Elham Baharzadeh (Annals of General Psychiatry, 2018)
Abstract Background The association of fruits and vegetables (FV) specific subgroups consumption and depression has not been investigated in healthy adult populations. Therefore, the aim of our study was to determine the relationship between intake of FV as well as their subgroups and depression. Methods This cross-sectional study was conducted on 400 women attending healthcare centers. The scores of depression, anxiety, and stress were measured using the 21-item depression, anxiety and stress scales questionnaire. The participants’ anthropometric and physical activity data were collected and the 147-item semi-quantitative FFQ was used for estimating the FV intake. Results After adjustment for confounding variables, the participants in the lower quartiles of total FV, total vegetables, total fruits, citrus, other fruits and green leafy vegetables intake were more likely to experience depression compared to those in the higher quartiles (p trend < 0.03). Conclusion Our findings suggest that higher intake of total FV and some of its specific subgroups might be associated with depression.